Islamic Religious Education Learning Based on Religious Moderation in Madrasah - M Munif; Aziz, Su'udin (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
Islamic Religious Education (IRE) learning in schools plays an important role in shaping students’ religious attitudes. However, in practice, IRE learning is still often focused on cognitive aspects and has not fully integrated the values of religious moderation. This condition may lead to an unbalanced understanding of religion and the emergence of intolerant attitudes among students. This study aims to describe the implementation of Islamic Religious Education learning based on religious moderation, students’ attitudes and understanding of religious moderation, and the role of IRE teachers in instilling religious moderation values at MTs Al Yakin Pungpungan. This research employed a qualitative approach with a descriptive design. The research subjects included Islamic Religious Education teachers and students of MTs Al Yakin Pungpungan. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that Islamic Religious Education learning at MTs Al Yakin Pungpungan has integrated religious moderation values through communicative, dialogical, and contextual learning approaches. Students demonstrate tolerant, open-minded, and respectful attitudes in social interactions. Islamic Religious Education teachers play a central role as role models and facilitators in instilling religious moderation values. The implications of this study suggest that Islamic Religious Education learning based on religious moderation needs to be continuously developed to strengthen character education and foster moderate religious attitudes in schools.